Garret D. Wall correspondence - Wall, Garret D. (Garret Dorset), 1783-1850.
ALS written by Wall to an unknown recipient relating to the nomination of Roger Brooke Taney to the Supreme Court, speeches by John C. Calhoun and Henry Clay in the Senate, a serious carriage accident, and social life in Washington, D.C.
Lawyer, army officer, jurist, and U.S. senator from New Jersey.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Calhoun, John C. -- 1782-1850.; Clay, Henry, -- 1777-1852.; Taney, Roger Brooke, -- 1777-1864.; United States. -- Supreme Court -- History; United States. -- Congress. -- Senate -- History; Carriages and carts -- Accidents -- Washington (D.C.); Washington (D.C.) -- Social life and customs; Army officers; Jurists; Lawyers; Senators, U.S. Congress -- New Jersey